Cultural Intervention: Helen Creighton’s Folksong Broadcasts, 1938-1939 - Webb, Jeff (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1992)
In 1938-1939 Helen Creighton produced a series of folksong broadcasts for the CBC. This essay examines these programmes and argues that Creighton attempted to intervene in working class culture. In her selection of repertoire, musical arrangement, commentary, and the programme format she tried to reform folk culture to conform to elite aesthetic standards. Following the methodology of the English folksong collector Cecil Sharp, she used the CBC folksong broadcasts to form a folk basis for a new “national” music.